Dampak Penerapan Teknologi terhadap Profitabilitas dengan Pengendalian Internal di Industri ABC di Indonesia - Sandrayati, Sandrayati; Wijayanti, Indah Oktari; Utami, Eva Yuniarti (Eastasouth Institute, 2024)
This study investigates the impact of technology implementation on profitability, taking into account the mediating role of internal control in the context of the ABC industry in Indonesia. Using a quantitative approach, this study collected data from a sample of 160 participants and used Structural Equation Modeling with Partial Least Squares (SEM-PLS) for analysis. Descriptive statistics, evaluation of measurement models, and results of structural models are examined. The findings show a significant positive relationship between technology implementation, internal control, and profitability. Analysis of the validity of the discriminant supports the peculiarities of the construct. This research contributes to an understanding of the complex interplay between technology adoption, internal control mechanisms, and financial performance in Indonesia's ABC industry. Implications for industry practitioners and avenues for future research are also discussed.